2003
DOI: 10.1002/chin.200329076
|View full text |Cite
|
Sign up to set email alerts
|

Azido‐Containing Aryl β‐Diketo Acid HIV‐1 Integrase Inhibitors.

Abstract: Oxocarboxylic acids and esters Oxocarboxylic acids and esters Q 0460Azido-Containing Aryl β-Diketo Acid HIV-1 Integrase Inhibitors. -Design and synthesis of a series of aryl β-diketo acids (I) carrying azido groups as novel HIV-1 integrase inhibitors are presented. -(ZHANG, X.; PAIS, G. C. G.; SVAROVSKAIA, E. S.; MARCHAND, C.; JOHNSON, A. A.; KARKI, R. G.; NICKLAUS, M. C.; PATHAK, V. K.; POMMIER, Y.; BURKE*, T. R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…Modeling of the azido-containing and benzyloxy-containing DKAs indicates that they are essentially superimposable, but the benzyloxy groups occupy more space (70). Interestingly, recent modeling studies have indicated that the azido-containing DKAs might bind to the active site of HIV-1 IN in two different modes: in addition to binding to HIV-1 IN in a manner similar to that of L-708,906, another mode of binding could take place in which the azido moiety, rather than the diketo moiety, participates in metal chelation (45).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Modeling of the azido-containing and benzyloxy-containing DKAs indicates that they are essentially superimposable, but the benzyloxy groups occupy more space (70). Interestingly, recent modeling studies have indicated that the azido-containing DKAs might bind to the active site of HIV-1 IN in two different modes: in addition to binding to HIV-1 IN in a manner similar to that of L-708,906, another mode of binding could take place in which the azido moiety, rather than the diketo moiety, participates in metal chelation (45).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, DKAs that contained one or two azido moieties exhibited potent and selective inhibition of the strand transfer reaction catalyzed by HIV-1 IN (46,70). The structures of the previously reported DKA L-708,906 (31), another structurally related benzyloxy-containing DKA (MB-DKA), and two azido-containing DKAs (DA-DKA and MA-DKA) are shown in Fig.…”
Section: Structures Of Azido-containing Dkas That Inhibit Hiv-1 Inmentioning
confidence: 90%
See 3 more Smart Citations